IMPLEMENTATION OF THE SLEBOR GAME IN IMPROVING THE ABILITY TO RECOGNIZE VOCABULARY IN GROUP A - Isnaini, Indri Dwi (Universitas Al-Hikmah Indonesia, 2024)
Appropriate efforts are needed to increase children's capabilities in introducing vocabulary. This is very important because humans use language for their daily lives. The world of children is a world of play, by playing children are free to express their feelings, so that children can get stimulation with good responses when playing. By continuing to be guided by the fact that early childhood children learn while playing. Therefore, to improve the ability to recognize vocabulary in this study, the game slebor was used. This research aims to determine the process of increasing the ability to recognize vocabulary through playing slebor in group A children of Tunas Bhakti Kindergarten using the PTK method with data collection techniques such as observation and documentation. The results obtained in implementing the slebor game to increase the ability to recognize vocabulary in Tunas Bakti Kindergarten children increased with results in the pre-cycle of 43%, increasing in cycle I by 50% at meeting I and at meeting 2 by 66%, meanwhile in cycle II increased by 74% at meeting 1 and 81% at meeting 2. Because by playing children become happy and happy so they are able to receive the stimulation provided in the game. The children from group A at Tunas Bhakti Kindergarten were very enthusiastic about this slebor game, however, they did not realize that by playing slebor they also learned vocabulary. This indicates that this slebor game is very influential in improving the capabilities of group A children in introducing vocabulary.